DERADIKALISASI DALAM PENANGGULANGAN TINDAK PIDANA PERSPEKTIF UNDANG-UNDANG TERORISME DI INDONESIA - Samud Samud (IAIN Syekh Nurjati Cirebon, 2021)
Deradicalization has a wide range of meanings, starting from matters of belief, legal handling, to correctionalization as an effort to change